Acute Appendicitis Occurring in Dengue Fever: A Case Report and Review of the Literature - Ayobamidele Rasaq Kolapo; Boluwatife Oluwafayoyimika Johnson (Case Reports in Infectious Diseases)
Dengue fever is a disease caused by the dengue virus and it is present in many tropical countries, including Nigeria. Cases of acute abdomen have been reported in dengue fever and they include acute cholecystitis, acute pancreatitis, acute appendicitis, and nonspecific peritonitis. This case report illustrates a case of acute appendicitis in dengue fever and aims to describe the relationship between both conditions. We report a case of a 25-year-old lady who presented with symptoms of dengue fever and was confirmed to have the disease. She was on treatment for dengue but subsequently developed acute appendicitis. She later underwent appendectomy and the appendix was confirmed to be inflamed both intraoperatively and histologically. Dengue virus can cause periappendiceal inflammation (periappendiceal fluid collection and mesenteric lymphadenopathy/adenitis) or acute appendicitis (which can progress to appendiceal perforation or appendicular mass formation). Periappendiceal inflammation presents with clinical features mimicking acute appendicitis but without appendicitis on ultrasonography or laparoscopy. Periappendiceal inflammation can also progress to appendicitis. For patients with dengue fever, diagnosis of acute appendicitis should not be based on clinical findings alone. Serial ultrasonography to confirm appendicitis is recommended. Conservative treatment with antibiotics should be the first line for acute appendicitis in dengue fever or periappendiceal inflammation in dengue. Surgical treatment is required in cases of appendiceal perforation or failure of conservative management.